ANALISIS TEORI HEALTH PROMOTION MODEL DENGAN PERILAKU PENCEGAHAN KEPUTIHAN PADA REMAJA PUTRI DI SMAN 3 KOTA JAMBI - Imelda, Imelda; Susilawati, Enny; Sari, Lia Artika; Kusmaryati, Pauline; Wahyuni Andrian, Karmila (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Vaginal discharge prevention behaviors are one of the priorities to optimally improve reproductive health in adolescents. This research is an analytical descriptive study with a cross-sectional approach. The population in this study was young women at SMAN 3 Jambi City in 2022 as many as 400 respondents, sampling using random sampling techniques using the Solvin formula as many as 80 respondents. The study was conducted from January-June 2022. Data collection is carried out by filling out a questionnaire using a google form by respondents. Data processing in this study used univariate and bivariate analysis with Chi-Square statistical tests. The results of the study obtained as many as 70 (87%) respondents behaved well, as many as 70 (87%) respondents had high self-motivation, as many as 74 (92%) respondents had high perceived benefits, as many as 44 (55%) respondents had high family and peer support, as many as 57 (71%) respondents had a strong commitment to action, there was a relationship of self-motivation, perceived benefits, family and peer support, and commitment to actions towards whitish prevention behavior in young women at SMAN 3 Jambi City in 2022. It is hoped that the results of this study can provide information for SMAN 3 Jambi City about the incidence of vaginal discharge and can immediately carry out early detection, especially for students at SMA N 3 Jambi City, as well as be used as a reference source regarding the analysis of vaginal discharge prevention behavior in young women based on the Health Promotion Model Theory.